Identification of G-quadruplex structures in MALAT1 lncRNA that interact with nucleolin and nucleophosmin - Ghosh, Arpita; Pandey, Satya Prakash; Joshi, Dheeraj Chandra; Rana, Priya; Ansari, Asgar Hussain; Sundar, Jennifer Seematti; Singh, Praveen; Khan, Yasmeen; Ekka, Mary Krishna; Chakraborty, Debojyoti; Maiti, Souvik (Nucleic Acids Research, 2023)
Nuclear-retained long non-coding RNAs (lncRNAs) including MALAT1 have emerged as critical regulators of many molecular processes including transcription, alternative splicing and chromatin organization. Here, we report the presence of three conserved and thermodynamically stable RNA G-quadruplexes (rG4s) located in the 3 & PRIME; region of MALAT1. Using rG4 domain-specific RNA pull-down followed by mass spectrometry and RNA immunoprecipitation, we demonstrated that the MALAT1 rG4 structures are specifically bound by two nucleolar proteins, Nucleolin (NCL) and Nucleophosmin (NPM). Using imaging, we found that the MALAT1 rG4s facilitate the localization of both NCL and NPM to nuclear speckles, and specific G-to-A mutations that disrupt the rG4 structures compromised the localization of both NCL and NPM in speckles. In vitro biophysical studies established that a truncated version of NCL (& UDelta;NCL) binds tightly to all three rG4s. Overall, our study revealed new rG4s within MALAT1, established that they are specifically recognized by NCL and NPM, and showed that disrupting the rG4s abolished localization of these proteins to nuclear speckles